Does method of closure effect cesarean wound healing? Stapler versus absorbable sub-cuticular closure done in a tertiary hospital, Nepal - Shrestha, Reena; Pradhan, Binita; Duwal Shrestha, Sarada; Pradhan Malla, Anagha (Journal of Patan Academy of Health Sciences, 2022)
Introduction: Postoperative wound complications for women undergoing cesarean delivery constitute a major cause of morbidity. Data on wound healing based on the type of cesarean wound closure is limited. In this study, we assess the outcome of stapler versus absorbable sub-cuticular suture for skin closure of the cesarean wound.Method: Prospective observational study. All cesarean section patients during the period of six months (Dec 2019 to May 2020) at Patan Hospital, Nepal, whose skin closure was done by sub-cuticular suture or stapler technique were recruited in the study. Ethical approval was obtained. These patients were followed up postoperatively on the 10th day for wound outcome (redness, edema, hematoma, seroma, discharge, gaping). Number and proportion were calculated, chi-square test, and Fisher’s exact test at 95% confidence interval were used to see the association and p